High individual variability in LDL-reductions after inclisiran administration in a "real-world setting". (3rd October 2022) - Makhmudova, U; Schatz, U; Kassner, U; Axthelm, C; Rohn, B; Westhoff, T; Vogt, A; Scholl, M; Stach, K; Sinnig, D L; Stuerzebecher, P; Schulze, P C; et al.
Abstract: Background and aims: Inclisiran inhibits hepatic synthesis of proprotein convertase subtilisin-kexin type 9 (PCSK9) (1). Previous studies suggest that inclisiran provides sustained reductions in low-density lipoprotein (LDL) cholesterol levels with infrequent dosing. Patients included in the ORION program received inclisiran on top of maximally tolerated statin therapy and demonstrated a profound 50% LDL-C reduction as early as 3 months (2). The aim of this retrospective, multi-center analysis was to use individual patient data to determine the extent of the variability in LDL-C reduction in response to inclisiran administration in a real-world setting. Methods: Since February 2021 the German Inclisiran Network (GIN) enrolled patients who received inclisiran due elevated LDL-cholesterol (LDL-C) levels in German lipid clinics. In contrast to patients included in the ORION program inclisiran could be administered to a broad range of patients with elevated LDL-C levels, including patients naive of lipid-lowering drugs, as well as patients on apheresis who failed to attain LDL-C goals. Results: In 10 lipid clinics in Germany a total of 117 consecutive patients received inclisiran. Patients, who were not on stable lipid-lowering medication at least 3 months prior to inclisiran administration, were excluded. Thus, a total of 61 patients were analyzed. Mean LDL-C level at baseline was 151.86±64.31 mg/dl (95 percent confidence interval (CI): 135.39 to 168.33 mg/dl). After 3 months, inclisiran reduced LDL-C levels by 34.6% (95% CI: 29.3 to 39.8%), mean LDL-C levels were 103.26±60.36 mg/dl (95% CI: 87.8 to 118.72 mg/dl). At baseline 18 (30%) patients received statins, 22 (36%) ezetimibe and 13 (21%) bempedoic acid. Twenty-five (41%) patients were not on any lipid lowering therapy at baseline and 15 (25%) were on apheresis and failed to attain LDL-C target levels at baseline. Altogether there was a high inter-individual variability in LDL-C reduction 3 months after the first administration of inclisiran (Figure 1). Interestingly, patients who received statins at baseline demonstrated a trend towards a more profound LDL-C reduction (42.6±20.6 vs. 30.33±19.2%). This effect, however, was not significant. Two patients did not demonstrate any LDL-C reduction after the first administration. Inclisiran was well tolerated. Only one patient reported a minor injection-site reaction. No further side-effects were reported. Conclusion: These results indicate that there is substantial individual variability in the LDL-C reduction after the first administration of inclisiran. Inclisiran was well tolerated without any serious side-effects. A longer follow-up period and further research is warranted to elucidate reasons for the high inter-individual variability in LDL-reductions in this real-world setting. Funding Acknowledgement: Type of funding sources: None.